Pengembangan Metode Project Based Learning â€œRuang Literasiâ€ untuk Peningkatan Keterampilan Menulis Artikel Ilmiah Mahasiswa Melalui Model Hybrid Learning - Saâ€™diyah, Ilmatus; Safitri, Eristya Maya; Arta, Safira; Irawan, Putri Nur Fadilah; Wulandari, Fitri; Ahmadi, Anas (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The study of writing is a study that attracts the attention of researchers, especially in the field of language. . In this regard, this research aims to develop learning methods that can improve the quality and writing skills of students’ scientific papers. The development method (R & D) which includes the stages: definition, design and development to test the effectiveness and quality of the PBL learning method "Literacy Space" was used in this research. The implementation of the development stage is carried out through a hybrid learning model. The data in this research is in the form of quantitative and qualitative data originating from student grades and student responses. Based on the research results, the "Literacy Space" PBL method shows that the "Literacy Space" PBL method has very good quality because it can improve scientific article writing skills among students and effectively applied in Indonesian language classes. A hybrid learning model also supports the effectiveness of this learning method.